PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, KECERDASAN EMOSIONAL, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI; Studi Pada Kantor Kecamatan Tanjung Selor Dan Tanjung Palas - Jonilius (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2026)
This study aims to examine the effects of leadership, organizational culture, emotional intelligence, and job satisfaction on employee performance at the District Offices of Tanjung Selor and Tanjung Palas. The research adopts a quantitative approach using a survey method. Data were collected through questionnaires distributed to 60 district office employees. Multiple linear regression analysis was employed to analyze the effects of each independent variable on employee performance. The results indicate that leadership, organizational culture, emotional intelligence, and job satisfaction simultaneously influence employee performance. Partially, leadership, organizational culture, and job satisfaction have a significant effect on employee performance, while emotional intelligence does not have a significant effect. These findings are expected to provide practical contributions for district government institutions in improving employee performance by strengthening leadership, organizational culture, and job satisfaction.